Study of Sex Wise Frequency of Specific Intestinal Parasite in Muzaffarpur, (Bihar) - Kiran,; Faiyaz Ahmad, (International Journal of Scientific Research in Science and Technology, 2025)
Sex wise analysis in this study revealed that insignificant higher prevalence in males as compared to female. The species wise frequency of Protozoan and helminths was studied in both the sex. The Giardia lambalia was highest prevalence in 1375 samples (10.22 percent) whereas Trichomonas hominis (30 sample) was 0.98 percent. Among helminths in wale the Ascaris lumbricoides frequency was high 35.97 percent of 4565 sample. Where as strongyloides prevalence were low 0.5 percent out of 68 specimens.
Keywords: Protozoan Prevalence; Helminthes; Intestinal Parasites